Preliminary Assessment of Geohazards’ Impacts on Geodiversity in the Kratovska Reka Catchment (North Macedonia) - Bojana Aleksova; Tin Lukić; Ivica Milevski; Dušan Puhar; Slobodan B. Marković (Geosciences, 2024)
This comprehensive study investigates the intricate interplay between geodiversity, geohazards, and anthropogenic influences within the Kratovska Reka catchment—an area distinguished by its remarkable geosites. Kratovska Reka, spanning a length of 17.3 km, serves as the left tributary to Kriva Reka. The watershed of Kratovska Reka, covering an area of 68.5 km2, is situated on the northwestern inclines of the Osogovo Mts in North Macedonia. Despite harboring exceptional geodiversity, the area lacks protective measures for its myriad geosites. Evaluating susceptibility to geohazards, including excessive erosion, landslides, and flash floods, this research identifies heightened risk zones, particularly in the valley of Kratovska Reka and its tributaries. A multi-hazard model reveals that 56.07% of the basin is vulnerable to geohazards. The study correlates lithological composition, relief features, and morphometric characteristics with geohazards, emphasizing the significance of paleovolcanic relief in resisting excessive erosion. Human-induced factors, notably deforestation and inappropriate land use, amplify geohazards. This research underscores the urgent need for geosite protection and sustainable land management to mitigate geohazards’ impacts. Additionally, it explores the correlation between land use practices and geodiversity, emphasizing the importance of responsible land management in safeguarding the geological and geomorphological values of the researched area.